2018
DOI: 10.1016/j.toxrep.2018.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and cytotoxic effect of biogenic silver nanoparticles on mitotic chromosomes of Drimia polyantha (Blatt. & McCann) Stearn

Abstract: HighlightsSynthesis of AgNPs by leaf extract of G. floribunda.Inhibition of mitotic index (MI) at higher concentration of AgNPs.Cytotoxic effect is directly proportional to the concentration of AgNPs.Higher concentrations of silver nanoparticles induce significant inhibition of root meristem activity and DNA damage causing cell death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 63 publications
(69 reference statements)
5
20
0
Order By: Relevance
“…The results of the Allium cepa assay were consistent with those obtained in a similar trial using the plant species Drimia polyantha , where decreases of the mitotic index and the presence of chromosomal alterations were found following exposure to the highest concentrations of biogenic silver nanoparticles synthesized using the plant Getonia floribunda 61 . Similar results were obtained using the Allium cepa assay to evaluate the effects of low concentrations of silver nanoparticles synthesized using the plant Swertia chirata 62 .…”
Section: Resultssupporting
confidence: 85%
“…The results of the Allium cepa assay were consistent with those obtained in a similar trial using the plant species Drimia polyantha , where decreases of the mitotic index and the presence of chromosomal alterations were found following exposure to the highest concentrations of biogenic silver nanoparticles synthesized using the plant Getonia floribunda 61 . Similar results were obtained using the Allium cepa assay to evaluate the effects of low concentrations of silver nanoparticles synthesized using the plant Swertia chirata 62 .…”
Section: Resultssupporting
confidence: 85%
“…There are also some reports on the genotoxic effects of AgNPs in Tradescantia paludosa, Vicia faba, Hordeum vulgare, Crepis capillaries, Pisum sativum, Allium sativum, Drimia indica, etc. [27,28]. Researchers have revealed that the A. cepa system is considered to be the best-established system, which is correlated considerably with the studies performed in eukaryotic and prokaryotic systems for evaluation of genotoxicity in vitro and in vivo [29].…”
Section: Introductionmentioning
confidence: 89%
“…Contrarily, accumulating evidences showed AgNP-induced toxicological effects in aquatic ecosystem, causing lethal damage to aquatic plants, aquatic microbes and aquatic vertebrates [33], as well as bacteria and non-mammalian animal species [17,34]. In addition, several investigations using in vitro models, further demonstrated size-, dose- and cell-dependent nanosilver cytotoxicity and genotoxicity, including chromosomal abnormalities and inhibition of mitotic processes [17,[35], [36], [37], [38], [39]].…”
Section: Introductionmentioning
confidence: 99%